Teaching Anticorruption - Stachowicz-Stanusch, Agata (Business Expert Press, 2013)
Ebook from IG Library ; The movement in management education towards a more serious concern with how corruption can be tackled has occurred in reaction to highly publicized corporate scandals and instances of management misconduct. Widespread scandals have eroded public faith in companies and public authorities, as well as fueled legislative reactions such as the Sarbanes-Oxley and Dodd-Frank acts in the United States, and the recent UK Bribery Act.The movement in management education towards a more serious concern with how corruption can be tackled has occurred in reaction to highly publicized corporate scandals and instances of management misconduct. Widespread scandals have eroded public faith in companies and public authorities as well as fuelled legislative reactions such as the Sarbanes-Oxley and Dodd-Frank acts in the United States, not to forget the recent UK Bribery Act. Concomitantly, management scholars and educators have begun to question the assumptions underlying traditional management education, which in their view not only contributed to the recent financial and moral crisis but also failed to prepare students and executives for coping with the leadership challenges and ethical dilemmas that face any responsible manager in contemporary corporations. We believe that the statement ' a prepared mind favors ethical behavior' carries some important truth to it and have therefore invited a group of world-class scholars with a diversity of backgrounds and perspectives to develop our thinking on how teaching in anti-corruption practices can be conducted today. How to teach anti-corruption in business schools and universities is not an area that has received much scholarly attention. Widely publicized corporate scandals have pushed public trust in business to an all-time low; and have raised the question about the role and effectiveness of university education in developing moral competencies among students -future business leaders. Our book is clearly a response to this situation. This book therefore sets out to develop an empirical and theoretical platform for rethinking business school curricula, with a specific view to understanding and meaningfully confronting the challenges of corruption of the second decade of the twenty-first century. In particular, the book will * offer examples of new tools, teaching methods and case studies for anti-corruption teaching * explore and discuss how particular approaches, such as Giving Voice to Values, may be used worldwide for teaching anticorruption * explore and discuss how curricula can be streamlined and rejuvenated in order to ensure a high level of integrity in the worlds of business